Bibliometric, network, and thematic mapping analyses of metaphor and discourse in COVID-19 publications from 2020 to 2022 - Alkhammash, Reem (Frontiers in Psychology, 2023)
The research contributions of metaphor as part of (critical) discourse studies have flourished during COVID-19; hence, it is necessary to consider their progress and foresee their future growth. To obtain a comprehensive understanding of COVID metaphor research in discourse and to identify the most recent research foci, bibliometric, network, thematic mapping and word cloud analyses were conducted in this study. The results showed that (1) research on COVID metaphors is largely shaped by Critical Discourse Analysis research approaches and methodologies; (2) the research production has investigated traditional genres such as news and emerging genres, including social media and multimodal data; and (3) research highlights the role played by metaphors in persuasion in public discourse. The findings of this study can assist future research in this or related fields by providing an overview of metaphor research in crisis communication.